Components Of The Methodology For Developing Independent Work Communication Skills In Future Primary Teachers - Ganiyeva, Nargiza Alijonovna; Egamkulova, Malikabonu (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the structural components of the methodology for developing communicative skills for independent work in future primary school teachers. The formation of communicative skills in the process of independent work is considered an important factor in the development of a teacher’s professional training, communication culture and pedagogical skills. According to the results of the study, the main components of the methodology are motivational-communicative, cognitive, practical and reflexive-evaluative components, the interconnection of which serves to form effective communicative competence in future teachers. The article also highlights the impact of these components on the professional development of the teacher’s personality, their importance in the process of organizing independent activity.